2003
DOI: 10.1590/s1135-57272003000600005
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics upon Hospital Release of Immigrants in the City of Valencia, Spain (2001-2002)

Abstract: Rev Esp Salud Pública 2003; 77: 713-723 N.º 6 -Noviembre-Diciembre 2003 Resultados: Recuperamos 8.444 ingresos que identificaron 1.577 ingresos de inmigrantes. Se evidenció una proporción similar de inmigrantes registrados con documentación reglada (841, 51,16%) e inmigrantes supuestamente no regularizados (803, 48,84%). Predominaron las mujeres (68,3%) frente a los varones (31,7%) y una media de edad inferior a los 30 años. El diagnóstico de alta más frecuente fue «complicaciones del embarazo, parto y puer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…Despite the increase in recent years in the number of studies directed at analysing the health of immigrants, these studies tend to focus on medical aspects such as the prevalence of different diseases and conditions among foreign nationals, care procedures to be applied and mortality rates, among others [2,3,16-20]. However, there are very few studies aiming to discover the repercussions of providing health care to immigrants inside the health service, with a view to directing health policies and improving care.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increase in recent years in the number of studies directed at analysing the health of immigrants, these studies tend to focus on medical aspects such as the prevalence of different diseases and conditions among foreign nationals, care procedures to be applied and mortality rates, among others [2,3,16-20]. However, there are very few studies aiming to discover the repercussions of providing health care to immigrants inside the health service, with a view to directing health policies and improving care.…”
Section: Introductionmentioning
confidence: 99%
“…These data were similar to those reported by Cots et al [13] at the Hospital del Mar in Barcelona during 2002 and 2003, where 9.1% of hospital admissions were by immigrants. Salazar et al [14], in the city of Valencia during 2002, reported that 18% of admissions were FCLICs. Ben Cheikh et al [17] reported that 3.7% of hospitalizations at hospitals in the Aragon Community from 2004 to 2007 were FCs.…”
Section: Discussionmentioning
confidence: 99%
“…This is because these individuals were either included within the AC group [13], were excluded [14], or were few in number and represented only 4.6% of all hospitalizations [17]. The profile of FCHICs was of adults with median ages similar to ACs, but with more males than females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por lo que respecta diferencias en el uso de recursos sanitarios, y como hemos comentado, la colaboración durante la hospitalización es buena, aunque el seguimiento posterior en ocasiones no lo es tanto. Es frecuente que se haga caso omiso de los consejos y diagnósticos, la falta de adherencia al tratamiento o el abandono y la no asistencia a citas posteriores, etc., lo que concuerda con otros estudios (Salazar et al, 2003;López de Dicastillo y Cheung, 2004). Estas circunstancias habría que valorarlas nuevamente en el marco de la situación social y económica y cultural así como a tenor del funcionamiento de barreras de acceso particulares para un gran contingente de población inmigrante.…”
Section: Discussionunclassified